2022
DOI: 10.1111/acel.13592
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of unfolded protein response prevents post‐anesthesia neuronal hyperactivity and synapse loss in aged mice

Abstract: Delirium is the most common postoperative complication in older patients after prolonged anesthesia and surgery and is associated with accelerated cognitive decline and dementia. The neuronal pathogenesis of postoperative delirium is largely unknown. The unfolded protein response (UPR) is an adaptive reaction of cells to perturbations in endoplasmic reticulum function. Dysregulation of UPR has been implicated in a variety of diseases including Alzheimer's disease and related dementias. However, whether UPR pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Both of these changes favor heightened pyramidal neuron activity. These findings align with previous reports of increased pyramidal neuron activity in the prefrontal cortex of aged mice during emergence from sevoflurane anesthesia 27 . Additionally, other research groups have reported enhanced pyramidal neuronal activity following isoflurane anesthesia, which involves modulation of GABAergic boutons of PV interneurons 58 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both of these changes favor heightened pyramidal neuron activity. These findings align with previous reports of increased pyramidal neuron activity in the prefrontal cortex of aged mice during emergence from sevoflurane anesthesia 27 . Additionally, other research groups have reported enhanced pyramidal neuronal activity following isoflurane anesthesia, which involves modulation of GABAergic boutons of PV interneurons 58 .…”
Section: Discussionsupporting
confidence: 92%
“…For example, repeated exposure of young or adult mice to sevoflurane, a commonly used inhalational anesthetic, induces tau hyperphosphorylation in the hippocampus, leading to cognitive impairment 22–26 . In aged mice, a single exposure to sevoflurane anesthesia results in a more than twofold increase in tau phosphorylation in the frontal cortex 27 . Furthermore, in patients, the incidence and severity of postoperative delirium have been linked to levels of total and phosphorylated tau in the serum, 28,29 while increased functional magnetic resonance imaging (fMRI) activity in the hippocampus of healthy older adults has shown a correlation with tau levels in cerebrospinal fluid (CSF) 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…S6E). Consistently, neuronal excitotoxicity has been confirmed to induce neuronal death after anesthesia [ 24 ]. The associated primers and fragments are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 82%
“…In addition, only the differentiation of NSCs into neurons was studied, and the differentiation of NSCs into oligodendrocytes, for example, was not assessed. Moreover, while we utilized the sevoflurane concentrations used in our previous study, 22 clinically relevant concentrations, and those commonly used in vitro experiments, 43,44 we did not test the full range of sevoflurane concentrations. Finally, as the association of HDAC9 with CREB in neural stem cells after sevoflurane exposure is a new finding in our study, the mechanism of interaction remains to be further investigated.…”
Section: Of 15mentioning
confidence: 99%